Interpersonal Meaning Analysis of Taylor Swift’s Song “Anti-Hero” - Yonarius Widyo Putra; I Gusti Ayu Mahatma Agung (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2023)
Song is a work of art created by humans and used for entertainment or a means to express and reveal the contents of the heart. By using songs, many people try to say something or convey a message to someone from the bottom of their hearts. The purpose of this research is to find out the interpersonal meaning of Taylor Swift’s Song “Anti-Hero”. This research applied a qualitative method to analyze 15 lyrics of the “Anti-Hero” song. This research is based on the theory of interpersonal meaning proposed by Halliday. The result showed that the song “Anti-Hero” by Taylor Swift used interpersonal meaning elements of Mood and Residue in the lyrics. Therefore, it can be concluded that the song “Anti-Hero” used interpersonal meaning to explain the meaning of the song to the listeners to show the feelings, emotions, and ideas of the songwriter. This helped the songwriter in creating a more meaningful connection between the music and the listeners.